IMPLEMENTASI KRIPTOGRAFI KOMBINASI ALGORITMA VIGENERE CIPHER DAN REVERSE CIPHER UNTUK KEAMANAN TEKS PADA APLIKASI CATATAN PRIBADI BERBASIS ANDROID - Siregar, Muhammad Faisal; Hasugian, Abdul Halim; Suhardi, Suhardi (Smart Education, 2024)
Abstract: Cryptography (Cryptography) is the science and art of keeping messages safe. (Cryptography is the art and science of keeping messages secure)